Estudo teórico da forma de linha de absorção do poli(p-fenileno vinileno) - Silva, Marcelo Castanheira da (2013)
In this work we made a theoretical study of absorption line-shape of poly (pphenylene vinylene) (PPV). The model was applied in films processed by techniques: spin-coating (SC), layer-by-layer (LbL), and Langmuir-Blodgett (LB). The probability of electronic transitions was calculated based on the molecular model of excitons, Franck-Condon states, Gaussian distribution of non-entangled chains with conjugate degree n, semi-empirical parameterization of energy gap, electric dipole moment, and electron-vibrational mode coupling. Based on the approach of the energy gap functional dependence 1/n, the inclusion of the non-homogeneity energy dispersion 1/n2 is essential to obtain good experimental data agreement, mainly, where the absorption spectra display peaks width of about 65 meV. For unresolved absorption spectra, such as those observed for a large number of conjugated polymers processed via spin-coating technique, for example, the non-homogeneity energy dispersion parameterization is not significant. We develop a model to describe the possible chemical reactions of conversion of poly(xylyliden tetrahydrothiophenium chloride) (PTHT) monomers to PPV monomers and PPV monomers in others monomers of different degrees of conjugation. The dependence 1/n of the functional energy gap was compared with experimental data oligomers and calculations optimized geometry by Density Functional Theory (DFT). Effects of exciton confinement were considered in the transition dipole moment functional. Simulations to calculate the oscillator strength of the absorption spectra in PPV oligomers indicate that the HOMO-LUMO state prevails over other excited states. Results obtained from the use of the distribution of the random walk are as good as those achieved by the use of Gaussian distribution of conjugated segments in simulations of absorption spectra of the PPV. The use of transition dipole moment functional, which includes the effect of exciton confinement together with the distribution of the random walk provide good results in adjustments theoretical absorption spectra of PPV with more consistent physical parameters.